Russell's Sundries Ben Franklin (Cimarron, New Mexico Cimarron Legend, 1992)
Advertisement for Russell's Sundries Ben Franklin in Cimarron, New Mexico.
Master List item # 63
File location is in the Raton File Cabinet
Keywords: Russell's Sundries Ben franklin; Wreath; Gemini Video tape; Hot glue gun; Plastic Canves; Cimarron, New Mexico